2015
DOI: 10.5964/ejop.v11i4.896
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Attractiveness and Status on Personality Evaluation

Abstract: Research on personality has shown that perceiving a person as attractive fosters positive expectations about his/her personal characteristics. Literature has also demonstrated a significant link between personality traits and occupational achievement. Present research examines the combined effects of attractiveness, occupational status, and gender on the evaluation of others’ personality, according to the Big Five model. The study consisted of a 2 (Attractiveness: High vs. Low) x 2 (occupational Status: High v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Vaillancort (2013) described the actions one takes to maintain status within one's gender as "intrasexual competition". For women, this may include indirect aggressive behavior which highlights self and passively devalues (i.e., isolates, give negative appraisals, speak ill of) women they find more attractive/threatening with the ultimate goal to gain/sustain social status and appeal to males/mates/those in authority (Dellesega, 2005;Fisher & Cox, 2009;Tartaglia & Rollero, 2015;Vaillancort, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Vaillancort (2013) described the actions one takes to maintain status within one's gender as "intrasexual competition". For women, this may include indirect aggressive behavior which highlights self and passively devalues (i.e., isolates, give negative appraisals, speak ill of) women they find more attractive/threatening with the ultimate goal to gain/sustain social status and appeal to males/mates/those in authority (Dellesega, 2005;Fisher & Cox, 2009;Tartaglia & Rollero, 2015;Vaillancort, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that in a speed dating context, when participants stay interested and want to exchange contacts with a potential partner to keep in contact in future, the perceived attractiveness will increase, and when they do not want it, it will not change. Many studies showed that knowing characteristics of a person changes the perception of attractiveness ( Tartaglia and Rollero, 2015 ; Gerlach and Reinhard, 2018 ). For example, both laboratory (e.g., Lewandowski et al, 2007 ) and naturalistic (e.g., Kniffin and Wilson, 2004 ) experiments show that personality and other non-physical characteristics affect physical attractiveness judgments.…”
Section: Introductionmentioning
confidence: 99%
“…A high level of agreement across individuals, cultures, and age groups has been found in terms of how attractiveness is perceived, yet there is still a debate about whether this reflects an innate preference ( Langlois et al, 1987 ), or common learning as a result of adaptation (e.g., Hahn & Perrett, 2014 ). Crucially, facial attractiveness appears to be highly valued in social exchanges, with evidence pointing to an advantage for attractive people in terms of how others perceive and judge them in social interactions and beyond ( Langlois et al, 2000 ; Mobius & Rosenblat, 2006 ; Riniolo, Johnson, Sherman, & Misso, 2006 ; Tartaglia & Rollero, 2015 ; Zebrowitz, Hall, Murphy, & Rhodes, 2002 ). Research has shown that people consider themselves more attractive than the average person ( Horton, 2003 ).…”
Section: Introductionmentioning
confidence: 99%